Hak atas Informasi bagi Konsumen untuk Mengetahui Daftar Harga Menu Makanan pada Usaha Kuliner - Zain, Reyvaldi; Astutik, Sri (Faculty of Law, University of Dr. Soetomo, 2023)
This study discusses the right to information for consumers to know the price list of food menus, in the perspective of UUPK. The purpose of this study is to analyze the problems that exist in the Flora Park in the city of Surabaya, by combining various legal materials with data obtained in the field. The object of this research is that almost every stall in the Surabaya City Flora Park area does not include prices on the menu list. The results of this study indicate that the right to price information regulated in UUPK tends to be business actors who do not know about this law. The reason why business actors do not include prices on the list of food menus is due to several different factors. The obligation to atone for their actions with accountability can be sanctioned in the form of civil compensation penalties and can be subject to criminal sanctions in the form of confinement in accordance with UUPK.